Pengaruh Citra Merek Dan Price Discount Terhadap Minat Beli Konsumen Di Tokopedia (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Buying interest is a consumer behavior which has the desire to choose, use, consume, or even want a product offered. The purpose of this study was to determine the effect of brand image and price discount on consumer buying interest at Tokopedia. This research was conducted in Gianyar Regency, the number of samples taken was 110 respondents using purposive sampling method. Data was collected through interviews and questionnaires which were then tested using validity and reliability tests, data analysis techniques used were classical assumption test, multiple linear regression analysis, determination, partial test with t test and simultaneous test with f test. Based on the results of the analysis, it was found that partially brand image (X1) has a positive and significant effect on consumer buying interest (Y), partially price discount (X2) has a positive and significant effect on consumer buying interest (Y) and there is a simultaneous positive and significant effect. variable brand image and price discount on consumer buying interest in Tokopedia. The results of this study can be suggested to Tokopedia to always pay attention to the professionalism of services in the application/website, to give discounts at least once a week and to continue to create strategies, especially in the field of marketing given the increasingly fierce competition.